Virtual Reality Mental Health Interventions in Geriatric Care for Functional or Well-being Enhancement – A Scoping Review - Li, Yijun; Muschalla, Beate (Die Rehabilitation, 2024)
Purpose It has become common to use Virtual Reality (VR) for mental health interventions; however, its use in care of the elederly is limited, especially regarding mood and well-being. In this review, we summarize the results of current VR-based mental health interventions for this population.Methods Peer-reviewed journal articles on immersive VR mental health intervention in seniors, published until 2022, were included.Results There were 2697 results found in the database search, of which 40 articles met the inclusion criteria and were included in the final analysis. Most studies did not use an experimental design with randomized controlled trials and follow-up sessions. Function-oriented and entertainment-oriented intervention studies were categorized. VR-based geriatric mental interventions have grown rapidly since 2018, especially the number of interventions that promote wellbeing. The function-oriented interventions used active interactions with varied devices. Entertainment-oriented interaction was primarily passive, seldomly using hand controllers for moving activities. Generally, VR interventions improved the mental health of older adults.Conclusion Geriatric rehabilitation can benefit from this innovative technology to maintain cognitive functions and to improve the well-being of seniors. They have potential for use in aging care and in retirement homes. Future VR interventions may also involve promoting social interaction to combat loneliness among seniors.
Keywords: older adults; immersive VR; review; intervention; mental health; geriatric rehabilitation; aging care